Fishes of Maurahi River at Jayraj Mau, Uttar Pradesh with a Note on Fishery Potential of Food and Ornamental Fishes - Pratima Singh (Journal of Indian Fisheries Association, 2020)
An attempt has been made to study fishes of the Maurahi River, a tributary of Ganga River, by undertaking a field survey and sampling at Jayraj Mau village in Unnao district of Uttar Pradesh, during October 2019. A total of 32 species belonging to 25 genera under 12 families and 6 orders were recorded. The fish fauna recorded belonged to the IUCN categories as endangered (1), vulnerable (1), near threatened (4), least concern (21), and not assessed (5). Among the orders, highest species diversity was observed for the order Cypriniformes with 17 species, 12 genera and 2 families followed by Siluriformes with 9 species, 7 genera and 5 families. Thus, Maurahi River has high fishery potential as it is blessed with many economically important food and ornamental species.